Osteoporotic fractures in patients with systemic lupus erythematosus and end stage renal disease. (January 2018) - Le, B; Waller, J L; Radhakrishnan, R; Oh, S J; Kheda, M F; Nahman, N S; Carbone, L
Background: The incidence of end stage renal disease (ESRD) in patients with systemic lupus erythematosus (SLE) is rising. However, the relationship between osteoporotic fractures and SLE in the setting of ESRD remains uninvestigated. The purpose of this study was to compare the frequency of incident osteoporotic fractures in patients with ESRD with and without SLE, to identify risk factors for fractures in patients with SLE and ESRD, and to examine the contribution of these fractures to mortality. Methods: Retrospective cohort study of patients with SLE ( n  = 716) and a 5% random sample of controls without SLE ( n  = 4176) in the United States Renal Data System (USRDS) from years 2006–2008 enrolled in Medicare Part D. Results: Fractures occurred in 10.6% ( n  = 76) of patients with SLE and ESRD and 12.1% ( n  = 507) of patients with ESRD without SLE ( p  = 0.24). Older age (adjusted relative risk 1.02, 95% confidence interval 1.01–1.04) was associated with an increased risk for fracture in patients with SLE and ESRD. In multivariable analyses, vertebral and hip fractures more than doubled the risk for mortality. Conclusions: The frequency of osteoporotic fractures in patients with SLE and ESRD is similar to the general population of patients with ESRD. Vertebral and hip fractures are significant contributors to mortality in patients with SLE and ESRD. Fracture prevention, in particular, for elderly patients with SLE and ESRD, should be considered. Summary: SLE is not an independent risk factor for fractures in patients with ESRD. However, among patients with SLE and ESRD, vertebral and hip fractures are significant contributors to mortality.